(untitled) (Damascus University Journal for legal sciences, 2024)
Commitment to abstain—sometimes called negative commitment—is a commitment under which a given person refrains from doing an act that he is normally permitted to do in the absence of the commitment. This may include the commitment to abstain from the right of competition, from marriage, or from building his/her own property to a certain level. Commitment by abstaining does not ask the abstained person to do something as it obliges the person to cease or refrain from doing a specific act. By doing so the abstained person will receive compensation. This research deals with the justification for the entitlement to compensation in the situation of commitment by abstaining despite not having to do any work. Anthropology scholars have already mandated this matter when the assigned person shows intention. When abstinence is accompanied by intent, it comes out of the circle of original nothingness. Given that the obligation to abstain is only intentional, it is actually considered as an act in itself and, thus, the committed person is entitled to compensation. In addition, the one who is committed to abstaining normally misses some earning as a result of his commitment to not do a particular act. Accordingly, an obligation to not earn or do something should lead to compensation.